Caesarean section rates in women in the Republic of Ireland who chose to attend their obstetrician privately: a retrospective observational study - Michael J. Turner; Ciara M. E. Reynolds; Léan E. McMahon; Eimer G. O'Malley; Michael P. O'Connell; Sharon R. Sheehan (BMC, 2020)
Abstract Background Caesarean section (CS) rates are increasing and there are wide variations in rates internationally and nationally. There is evidence that women who attend their obstetrician privately have a higher incidence of CS than those who attend publicly. The purpose of this observational study was to further investigate why CS rates may be higher in women who chose to attend their obstetrician privately. Methods This study analysed data collected as part of the clinical records by midwives at the woman's first antenatal appointment in a large European maternity hospital. All women who delivered between the years 2009 and 2017 were included. Data were analysed both cross-sectionally and longitudinally. Results Overall, 73,266 women had a singleton pregnancy and 1830 had a multiple pregnancy. Of the packages of maternity care, 75.2% chose public, 10.8% chose semiprivate and 14.0% chose private. During the study, 11,991 women attended the hospital for their first and second pregnancies. Overall, women who attended privately were older and had higher proportions of infertility treatment and history of miscarriage (all p < 0.001) compared to those publicly-funded. Private patients were more likely to have a history of infertility, a history of miscarriage, a multiple pregnancy and to be ≥35 yrs. They had lower rates of obesity, smoking and illicit drug use in pregnancy (all p < 0.001). In women who chose private care, the overall rate of CS was higher compared to women choosing publicly-funded (42.7% vs 25.3%, p < 0.001) The increase was due to an increase in elective rather than emergency CS. The increase in elective CS fell after adjustment for clinical risks. In the longitudinal analysis, 89.7% chose the same package second time around. Women who changed from public to private care for the second pregnancy were more likely to have had a previous emergency CS or admission to the Neonatal Unit. Conclusions This study suggests that the increased CS rate in women privately insured may be attributed, in part, to the fact that women who can afford health insurance choose continuity of care from a senior obstetrician because they are risk adverse and wish to have the option of an elective CS.